Manganese-doped gold core mesoporous silica particles as a nanoplatform for dual-modality imaging and chemo-chemodynamic combination osteosarcoma therapy. Issue 9 (2nd March 2021) - Sha, Zhou; Yang, Shuguang; Fu, Liwen; Geng, Mengru; Gu, Jiani; Liu, Xuying; Li, Shikai; Zhou, Xiaojun; He, Chuanglong
Abstract : The as-prepared nanoparticles integrate bone targeted chem-chemodynamic combination therapy and dual-modality computed tomography/magnetic resonance (CT/MR) imaging into a single platform. Abstract : In this study, an effective and facile strategy is reported to construct a multifunctional nanoplatform by in situ doping metal manganese on gold core mesoporous silica nanoparticles (Au@MMSN). After further modification of alendronate (Ald) on Au@MMSN, the obtained Au@MMSN-Ald efficiently integrates bone targeted chemo-chemodynamic combination therapy and dual-modality computed tomography/magnetic resonance (CT/MR) imaging into a single platform. In particular, Au@MMSN-Ald exhibits excellent tumor microenvironment responsive drug release efficiency. The doxorubicin hydrochloride (DOX) loaded Au@MMSN-Ald (DOX@Au@MMSN-Ald) is demonstrated with excellent targeted ability toward osteosarcoma. Accordingly, in a specific tumor microenvironment, DOX@Au@MMSN-Ald also displays outstanding combined efficiency for killing cancer cells in vitro and suppressing the osteosarcoma growth in vivo . Benefiting from the Au nanoparticles confined in the core and manganese ions released from the shell, CT and MR dual-modality imaging were performed to verify the effective accumulation of Au@MMSN-Ald at the tumor site. Overall, the constructed DOX@Au@MMSN-Ald nanoparticles integrated imaging guide, responsive drug release and combination therapy, which may provide some insight for further biomedical applications in efficient osteosarcoma therapy.